2009
DOI: 10.1111/j.1365-2141.2009.07611.x
|View full text |Cite
|
Sign up to set email alerts
|

The route to development of myelodysplastic syndrome/acute myeloid leukaemia in Shwachman‐Diamond syndrome: the role of ageing, karyotype instability, and acquired chromosome anomalies

Abstract: Summary An investigation of 22 new patients with Shwachman‐Diamond syndrome (SDS) and the follow‐up of 14 previously reported cases showed that (i) clonal chromosome changes of chromosomes 7 and 20 were present in the bone marrow (BM) of 16 out of 36 cases, but if non‐clonal changes were taken into account, the frequency of anomalies affecting these chromosomes was 20/36: a specific SDS karyotype instability was thus confirmed; (ii) the recurrent isochromosome i(7)(q10) did not include short arm material, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 24 publications
4
55
0
3
Order By: Relevance
“…First, we analyzed the relationships between the genotype and the occurrence of hematologic complications. Until now, only four studies [38][39][40][41] had reported both information about SBDS genotypes and a survey of patients including cases with SC. These four studies comprised 47 patients, among whom nine cases of malignant SC and two cases of non-malignant SC were observed, showing no particular association between genotype and SC.…”
Section: Discussionmentioning
confidence: 99%
“…First, we analyzed the relationships between the genotype and the occurrence of hematologic complications. Until now, only four studies [38][39][40][41] had reported both information about SBDS genotypes and a survey of patients including cases with SC. These four studies comprised 47 patients, among whom nine cases of malignant SC and two cases of non-malignant SC were observed, showing no particular association between genotype and SC.…”
Section: Discussionmentioning
confidence: 99%
“…We tested BM cells of five i(7)(q10)-positive SDS patients, identified as UPN (unique patient number) 24, 25, 32, 36, and 40 (the last patient was not included in Maserati et al, 2009). The results of the dual colour FISH showed that both the probes hybridized the centromeric region of the i(7)(q10) in all the patients, with different patterns: the probe D7Z1 showed two distinct separate signals on the i(7)(q10), exactly as we had already detected by FISH with the commercial probe, but also a signal referable to the probe D7Z2 was present.…”
mentioning
confidence: 99%
“…Ineffective erythropoiesis, marrow failure, neutrophils migration defect [91] MDS, AML with i(7)(q10) [92] Kostmann syndrome (severe neutropenia) Taken together, a general model of lymphomagenesis can be proposed that combines generation of illegitimate TCR/BCR recombination events with conditions that lead to expansions of the precursor pool (e.g., antigen stimulation, lymphotropic herpesvirus infection, immune hyper-responsiveness or germline defects in apoptosis). Thus, full emergence of lymphoid malignancies becomes more likely as the pool of preneoplastic lymphocytes with translocations expands.…”
Section: Factors Related To the Initiation Of Lymphomas And Leukemiasmentioning
confidence: 99%